Comparison of Phylogeny, Venom Composition and Neutralization by Antivenom in Diverse Species of Bothrops Complex - Sousa, Leijiane F. (Public Library of Science, 2013)
In Latin America, Bothrops snakes account for most snake bites in humans, and the recommended treatment is administration of multispecific Bothrops antivenom (SAB – soro antibotrópico). However, Bothrops snakes are very diverse with regard to their venom composition, which raises the issue of which venoms should be used as immunizing antigens for the production of pan-specific Bothrops antivenoms. In this study, we simultaneously compared the composition and reactivity with SAB of venoms collected from six species of snakes, distributed in pairs from three distinct phylogenetic clades: Bothrops, Bothropoides and Rhinocerophis. We also evaluated the neutralization of Bothrops atrox venom, which is the species responsible for most snake bites in the Amazon region, but not included in the immunization antigen mixture used to produce SAB. Using mass spectrometric and chromatographic approaches, we observed a lack of similarity in protein composition between the venoms from closely related snakes and a high similarity between the venoms of phylogenetically more distant snakes, suggesting little connection between taxonomic position and venom composition. P-III snake venom metalloproteinases (SVMPs) are the most antigenic toxins in the venoms of snakes from the Bothrops complex, whereas class P-I SVMPs, snake venom serine proteinases and phospholipases A(2) reacted with antibodies in lower levels. Low molecular size toxins, such as disintegrins and bradykinin-potentiating peptides, were poorly antigenic. Toxins from the same protein family showed antigenic cross-reactivity among venoms from different species; SAB was efficient in neutralizing the B. atrox venom major toxins. Thus, we suggest that it is possible to obtain pan-specific effective antivenoms for Bothrops envenomations through immunization with venoms from only a few species of snakes, if these venoms contain protein classes that are representative of all species to which the antivenom is targeted.